KUALITAS MINYAK PAUS SPERMA HASIL PENGAWETAN OLEH NELAYAN LAMALERA-LEMBATA MELALUI PENJEMURAN DI PANTAI - Gerardus Diri Tukan; Joanivita Paulo Gulo Soru; Maria Novalina Naben (JURNAL PERIKANAN TROPIS, 2026)
Lamalera fishermen in Lembata Regency traditionally hunt sperm whales (Physeter macrocephalus) and preserve the blubber by sun-drying it on the beach prior to barter trading. The oil extracted from this blubber is typically characterized by a strong fishy odor. This study aims to determine the quality of sperm whale oil produced through this traditional preservation method. The research employed an experimental method. Solid blubber samples (221.34 g) were processes using thermal extraction to obtain the oil. The research procedure included sample preparation, thermal extraction, and analysis of physical and chemical properties with all experimental performed in triplicate. Physical analyses included oil yield, moisture content, and density, while chemical analyses comprised free fatty acid (FFA) content (by alkalimetric titration), saponification value (by acid–base titration), and iodine value (by Wijs method). The results showed an oil yield of 76.65%, moisture content of 1.43%, and density of 1.051 g/mL at 32°C. Chemically, the oil had a free fatty acid (FFA) content of 8.95%, saponification value of 80.41 mg KOH/g, and iodine value of 9.86 g I₂/100 g oi1l.